English Phonological Interference by Indonesian Speakers in a MoFAâ€™s Media Briefing - Richa Noer Hidayati; Dedi Sulaeman; Yatmikasari, Ika (Jurnal Bahasa Inggris Terapan, 2023)
Phonological interference occurs when a speaker reproduces the sound in the second language system but the use of the first language system is still recognized. This phenomenon is frequently found in the speech or utterances of second language speakers such as that of presented in a video from Indonesian Minister of Foreign Affairâ€™s (hence MoFA) YouTube channel entitled â€œMedia Briefing of Covid-19 Vaccine Development in Indonesiaâ€. Thus, this study focuses on the phonological interference in the video by investigating its types based on particular characteristics of the categories. This research applies Weinreichâ€™s theory of phonological interference (1968) as the grand theory to answer the research problem and qualitative descriptive method as the research. The data collected are obtained by recording technique to combine the equivalence of the video recording and the transcript. The results show the findings on four types of phonological interference. They are under-differentiation of phonemes, over-differentiation of phonemes, reinterpretation of distinctions, and actual phone substitution.